ESTRATÉGIAS DE CONTROLE DE QUALIDADE PARA A DIFERENCIAÇÃO DE ESPÉCIES DO GÊNERO Kalanchoe - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The synergy between traditional knowledge and scientific rigor is essential for driving innovations in traditional medicine and herbal therapy. Considering the historical importance and the growing relevance of medicinal plants in contemporary pharmacology, this study presents an integrated analysis of species from the genus Kalanchoe, with an emphasis on the differentiation of species that are frequently used interchangeably in folk medicine. In this context, the study focuses on a detailed distinction and characterization of the species Kalanchoe crenata, Kalanchoe daigremontiana, Kalanchoe marmorata, Kalanchoe pinnata, and Kalanchoe x houghtonii, from morphoanatomical and chemical aspects. Through an in-depth pharmacobotanical approach, quantification of phenolic compounds, evaluation of antioxidant potential, and definition of the chemical profile by advanced chromatographic techniques, the methods employed, including high-resolution microscopy and modern chemical analyses, serve as essential tools for the quality control of plant extracts and derived products. The findings of this research highlight notable differences between the investigated species, contributing to better use in traditional medicine and the preparation of herbal medicines. Additionally, the study expands the understanding of the chemical composition and specific characteristics attributed to the Kalanchoe species, underscoring the importance of rigorous quality control procedures in the authentication of inputs, and ensuring the efficacy and safety of derived products.
Keywords: Medicina tradicional; Farmacobotânica; Fitoquímica; Química de Produtos Naturais; Controle de Qualidade em Fitoterápicos; Traditional medicine; Pharmacobotany; Phytochemistry; Natural Product Chemistry; Quality Control in Herbal Medicines; CNPQ::CIENCIAS DA SAUDE